Pendidikan Ibadah Anak Usia Dini Dalam Kitab Fasalatan Karya KHR. Asnawi - Nur Khosiin (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2020)
The fasalatan book is a form of Kiai Asnawi's concern for Muslims, especially for early childhood, in the context of forming a Muslim personality who always obeys and worships Allah, especially in terms of prayer. This study aims to reveal the contents of the book Fasalatan in the perspective of worship education for early childhood. This research is a library research with data collection methods through interviews and documentation and an interpretive descriptive approach. The primary data source is the book of Fasalatan, the secondary is related works. According to Kiai Asnawi, religious education in the form of prayer is important for children. He reminded the Muslims and their children to always pray five times a day because without doing the five prayers the Muslims and their children would suffer losses.